The Effects of Natural Antioxidant Extracts Supplementation on Performance and Meat Quality of Broiler Chickens - Ishola, Hakeem; Jiya, Elisha Zhiri; Adama, J.Y; Alabi, Olushola John (Journal of Agricultural Sciences (Belgrade), 2020)
The study examined the effect of dietary antioxidant supplementation on performance and meat quality of broiler chickens. 300 day old Abhor acre broiler chicks were fed starter diet from 1-4 weeks and finisher diet for the last 4weeks. Birds were randomly assigned to treatments based on antioxidants supplementation in drinking water at 0.02% butylated hydroxyanisole (BHA), ordinary water (OW), 0.02% sweet orange peel extracts (SOPE), 0.02% shaddock peel extracts (SHPE) and 0.02% lemon peel extracts (LMPE) per litre of water in a completely randomized design experiment. Feed intake and body weight gain were recorded on weekly basis. 3 birds were selected in each treatment and slaughtered for meat quality determination. Despite treatment (OW) having the best feed intake, which was significantly different (P<0.05) from other treatments, does not translate to better weight gain and feed conversion efficiency. Treatments BHA and LMPE had the best weight gain and feed conversion efficiency at significant level (P<0.05). There were significant differences (P<0.05) on the shear force (force peak and yield) on the dietary antioxidants fed to the birds. Sensory parameters (taste, aroma and overall acceptability) shows significant differences (P<0.05) amongst the treatments. However, there were no significant differences (P>0.05) on appearance and texture perception amongst treatments. Finally, significant differences (P<0.05) exist amongst the treatments on the lightness (L*) and redness (a*) of the meat samples. There were no significant differences (P>0.05) on the yellowness (b*) amongst the treatments. SOPE and SHPE can serve as a substitute for BHA on overall acceptability perception for meat quality evaluation.